PENGARUH TEMPERATUR EKSTRAKSI ZAT WARNA ALAM DAUN JATI TERHADAP KUALITAS DAN ARAH WARNA PADA BATIK - Satria, Yudi; Suheryanto, Dwi (Balai Besar Standardisasi dan Pelayanan Jasa Industri Kerajinan dan Batik, 2016)
Negative impacts especially synthetic dye carcinogenic effect on the environment and the user so natural coloring is now starting to be used because environmentally friendly. The influence of temperature variations on the quality and color direction using natural color teak leaves for batik cloth needs to be examined because the color of the fabric will decline due pelorodan process. The young leaves teak (Tectona grandis) have a wide and large size, used to dye woven materials, have reddish brown color. The method used was variation temperature extraction of 50°C, 75°C and 100°C, fixation of alum, lime, prusi and lotus as well as testing the quality and direction of color. Variations in temperature extraction of teak leaves on cotton fabric and silk using a waterbath expected to know the quality and direction of the colors in batik. Results of testing the fastness to light and washing 40°C for extraction of teak leaf temperature of 50°C, 75°C and 100°C in cotton and silk with fixation alum, lime, prusi or lotus shows good scale with a value of 4 or 4-5. Natural color solution teak leaves with extraction temperature of 100°C resulted in the highest wavelength is 788.50 nm and the absorbance of the total of 0.1402 Abs. Color direction that produced show reddish color will be more visible at 100°C with a fixation alum or lime while prusi or lotus browned.